PERGESERAN FUNGSI DAN KEDUDUKAN BADAN PERMUSYAWARATAN DESA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA (STUDI BPD DESA KUNJANG) - Galuh Candra Purnamasari (Refleksi Hukum: Jurnal Ilmu Hukum, 2019)
This research discusses the effect of shifting the function and the state of the Village Consultative Body according to Law No. 6 of 2014 on Village. The study particularly took an observation in Kunjang Village. The used method in this paper is normative research which applies legislation approach and historical approach. The final conclusion resulted by this research is the shift of function and the state of the Village Consultative Body had influenced the state of the Village Consultative Body Kunjang. First, the state of the Village Consultative Body Kunjang is no longer an element of village administration and as a "partner" of the headman. Second, the monitoring function becomes the only main function of the state of the Village Consultative Body Kunjang, whereas the legislative function becomes the duty of the Kunjang Village Government, stressing that the legislative function is not part of the main duty and responsibility of the Village Consultative Body Kunjang.